Chapter Introduction The complexity of the French principle of Laïcité - Portier, Philippe (Taylor & Francis, 2022)
This volume examines the perception of the French principle of laïcité or secularism and attempts to demonstrate to English-speaking readers that the configurations of the French model of laïcité are both more flexible and complex than they appear to be. Due to the diversification of France's religious landscape (notably with a Muslim minority estimated at 7% of the population) and some of the effects of Europeanisation, French secularism is being urged to shed its anti-religious tendencies and abandon a version of secularism conceived as an alternative to religion. The French Republic is not a secularist state but a secular state where secularism is conceived as a founding principle of pluralistic democracies.